Revisiting testicular torsion scores in an Asian healthcare system. Issue 6 (December 2020) - Lim, Xuxin; Angus, Mark Ian; Panchalingam, Vivekandan; Chng, Kim Im; Choo, Candy SC; Chen, Yong; Kannan Laksmi, Narasimhan
Summary: Introduction: Testicular pain is a common presentation amongst young boys. It is important to distinguish between testicular torsion and other testicular pathology as testicular viability is dependent on timely diagnosis and surgical intervention. Objectives: The aim of this study was to evaluate the utility of the TWIST score in our population. Our second objective was to compare a new testicular torsion score (TT score) developed in a paediatric Asian population, with the TWIST score in risk stratification for testicular torsion. Duration of symptoms and delays after presentation were also correlated with testicular viability. Methods: This is a prospective cohort study of children admitted with testicular pain from January 2016 to December 2018 at a tertiary care hospital in Singapore. Relevant findings such as age, nausea/vomiting, testicular swelling/firmness, absence of cremasteric reflex and abnormal lie were collected. Univariate and multivariate logistic regression was performed to identify significant predictive factors of testicular torsion to generate TT score. Results: A total of 315 patients were involved in this study. Mean age of patients was 121.3 ± 44.2 months. There were 43 patients with testicular torsion. No patients with a TT score of ≤1 were found to have testicular torsion. In contrast, 10 patients with a TWIST score of ≤2 were found to have testicular torsion. Of the patients with testicular torsion, 16 had a TWIST score of ≥5 and 22 had a TT score of ≥6. In this study, the area under the curve was 0.87 for the TWIST score and 0.93 for the TT score. Conclusion: In conclusion, the TT score is a reliable score for excluding testicular torsion in an Asian patient population with a sensitivity and negative predictive value of 100% at a cut-off value of ≤1. Both TWIST and TT score performed equally well in early presenters (<6 h) Further prospective validation studies are needed to evaluate the utility of the TT score. Delay in presentation to hospital is the most important determinant of outcome. Summary Table Proposed testicular torsion score (TT score). Summary Table Risk factor Score Age group (≤1 or ≥10 Years old) 1 Nausea or vomiting 2 Testicular swelling 2 Testicular firmness 1 Absent cremasteric reflex 1 Abnormal lie 2 The testicular torsion (TT) score. The score ranges from 0 to 9. A score of ≤1 indicates that, testicular torsion is unlikely while a score of ≥6 is predictive for testicular torsion.